Coreopsis tinctoria flowers extract ameliorates D-galactose induced aging in mice via regulation of Sirt1-Nrf2 signaling pathway. (September 2019) - Tian, Yong; Wen, Zhen; Lei, Lin; Li, Fuhua; Zhao, Jichun; Zhi, Qi; Li, Fuxiang; Yin, Ran; Ming, Jian
Graphical abstract: Highlights: A total of 12 active compounds were identified in CTE using UPLC/Q-TOF-MS. CTE showed superior antioxidant activities in vitro. CTE exhibited promising anti-aging effects against D -Gal induced aging in mice. The underlying mechanism might be related to up-regulation of Sirt1-Nrf2 signaling pathway by CTE. Abstract: The aim of this study was to investigate the protective effects and its underlying signaling pathways of Coreopsis tinctoria flowers extract (CTE) on D -galactose induced aging in mice. UPLC/Q-TOF-MS analysis of CTE identified 12 active compounds, including three phenolic acids and nine flavonoids. The extract showed superior antioxidant activities in vitro using DPPH, FRAP, and ORAC assay. Administration with CTE remarkably improved body weight, organ indexes of aging mice, and liver histological injury as well as decreased oxidative stress markers levels of aged mice. Further studies showed CTE treatment significantly enhanced Sirt1 expression and activated the Nrf2 signaling pathway by the increase of Nrf2 nuclear translocation, NQO-1 and HO-1 expression. Furthermore, CTE treatment resulted in the increase of Sirt3 and the suppression of p53. These results demonstrated that the promising anti-aging effects of Coreopsis tinctoria flowers extract might be related to up-regulation of Sirt1-Nrf2 signaling pathway.